The effect of knocking down Sec31A on the malignant phenotype of HNSCC - HE Yao, ZHAO Zhenyuan, GAO Teng, LIN Peng, CHEN Yiren, SONG Xiaomeng (Editorial Office of Stomatology, 2024)
Objective To explore the impact of knocking down Sec31A on the malignant phenotype of head and neck squamous cell carcinoma(HNSCC) and its possible mechanisms. Methods Transcriptome sequencing data of HNSCC tissues and adjacent tissues were obtained from the TCGA database, and the expression levels of Sec31A were compared. Immunohistochemical staining was used to analyze the expression of Sec31A in HNSCC tissues. Kaplan-Meier survival analysis was used to compare the relationship between Sec31A and the prognosis of HNSCC patients. Small interfering plasmids si-Sec31A and si-NC were transfected into HNSCC cell lines HN6 and HN4, and the impact of knocking down Sec31A on the biological behavior of HNSCC cells was detected through CCK-8 experiments, plate cloning experiments, scratch healing experiments, and Transwell experiments. Changes in the expression levels of PI3K/AKT/mTOR pathway related proteins in cells were detected after knocking down Sec31A with HN6 and HN4 through Western Blot(WB)experiments. Stable transfected cell lines of HN6 siSec31A and HN6 siNC were constructed and inoculated subcutaneously in nude mice to further verify the tumorigenic effect of Sec31A in vivo. Results TCGA data showed that Sec31A was higher in HNSCC tissues than in adjacent normal tissues(P<0.01), and high expression of Sec31A was significantly correlated with poor prognosis in patients(P<0.05). Immunohistochemical staining showed that Sec31A was expressed stronger in HNSCC tissues than in normal tissues. In HN6 and HN4 cells, knocking down Sec31A resulted in significantly weaker proliferation, migration, and invasion abilities compared to the control group. Through WB experiments, it was found that transfection of si-Sec31A with HN6 and HN4 significantly reduced the expression levels of p-PI3K, p-AKT, and p-mTOR proteins. After knocking down Sec31A with HN6, the transplanted tumor volume in nude mice was significantly smaller than that in the control group. Conclusion Knocking down Sec31A can inhibit the proliferation, migration and invasion of HNSCC cells, possibly through the PI3K/AKT/mTOR pathway.